Unravelling the G × E interactions using AMMI biplot for phenology and agro-morphological traits in linseed (Linum usitatissimum L.): UNRAVELLING G×E INTERACTIONS FOR PHENOLOGY AND AGRO-MORPHOLOGICAL TRAITS IN LINSEED - MITHLESH KUMAR,; MANUBHAI PATEL,; RAVINDRASINGH CHAUHAN,; CHANDRESH TANK,; SATYANARAYAN SOLANKI, (Journal of Oilseeds Research, 2022)
In the present study, additive main effects and multiplicative interactions (AMMI) biplot analysis was used to identify stable genotypes for days to flowering, maturity, plant height and number of branches per plant to dissect GEI in linseed (Linum usitatissimum L.). Trials were conducted in randomized complete block design (RCBD) with two replications over three consecutive years, 2016-17, 2017-18 and 2018-19. ANOVA analysis revealed genotype and G×E interaction effects contributed significant sum of square for days to flower (97.31% and 0.56%); days to maturity (89.27% and 8.90%); plant height (98.29% and 0.70%) and number of branches per plant (86.40% and 2.41% respectively). The dissection of GE interaction for all the traits was mostly explained by the first and second principal component axis (IPCA1 and IPCA2). The SSI statistic fully sync with the results of the AMMI1 biplot analysis for all the traits of top ranked genotypes across the environments. Results of genotypes stability in AMMI1 and AMMI2 biplot analyses were shown differential response with some exceptions that indicates the different sets of genes were responsible for the cumulative expression of traits under study. In the present study environments imposed variable effects with few exceptions towards the genotype stability in both AMMI1 and AMMI2 analysis models for all the traits studied. Hence, the desirable genotypes identified in linseed for phenology and agro-morphological traits could be utilized in hybridization program and varietal recommendation under semi-arid conditions.